Analisis Paracetamol dalam Sediaan Sirup X dan W dengan Metode Spektrofotometri UV-Vis Genesis 10s - Purba, Hermawan; Gresela, Paula; Manalu, Tiodora; Mayranti, Dwi; Zalukhu, Historis (Program Studi S1 Farmasi, STIKES Senior, Medan, 2024)
Paracetamol is a medication that is safe for children to use to relieve pain and reduce fever, with minimal side effects. This medication is available in various forms, including syrup, which consists of a solution with a high sucrose content. Maximum Wavelength and Calibration Curve: In the study, the standard paracetamol was analyzed to determine that the obtained wavelength is at 246 nm. Several solutions with different concentrations (10, 15, 20, 25, and 30 ppm) were used to create a calibration curve, which shows the relationship between absorbance and concentration. Linear regression equation: Y = 0.0044x – 0.0166, R² = 0.9936. The absorbance of the syrup sample indicates a paracetamol concentration of approximately 24.23 ppm for sample X and 17.63 ppm for sample W, calculated using a calibration curve. Thus, the research shows an effective analytical method for determining the concentration of paracetamol in syrup preparations.